Orientações curriculares nacionais : uma leitura sobre a materialização nos curículos de formação docente em educação física - Marques, Fabíola Borel (2013)
This research aims to investigate which methods of the prescribed curriculum of physical education teachers, to act in Basic Education, has interpreted and materialized the assumptions of the NationalCurriculum Guidelines for teacher formation. It problematizes the instructor’s formation in physical education, from the Brazilian legislation that regulates the degree courses for Basic Education, as well as the National Curriculum Guidelines for TeacherTraining for Basic Education in Higher Level: Feedback CNE/CP 009/2001, Resolution CNE/CP 01/2002, Resolution CNE/CP 02/2002 and Resolution CNE/CES 07/2004. In regards to the methodological approach, guided by assumptions of a qualitative study of documentary character, with analysis and interpretation of the prescribed curriculum of Physical Education for teacher training. The scope of the research field was defined, methodologically, in the field itself, allowed to be performed with three Higher Education Institutions (IES) in the State of Espírito Santo, identifies three different ways of concretizing the formation degree in Physical Education in the region. The IES A materializes degrees in Physical Education to meet basic education for four years. The IES B materializes the Bachelor Degree and licensing, in a course concurrently with the format of four years. The IES C materializes a BA degree and licensing, and the bachelor's degree is offered in the form of complementation course, in four years and six months on night shift, or four years in the afternoon shift. It concludes that the meanings and materializations in the studied curriculum are very different and, at times, ambiguous, for the readings and ways to interpret the National Curriculum Guidelines are in accordance with the instructor’s intention in physical education training that each IES seeks to socially consolidate